Pendidikan Akhlak Siswa dalam Kegiatan Ekstra - Umi Choiriah (Journal An-Nafs: Kajian Penelitian Psikologi, 2016)
This article aims to explain the implementation of moral education of students through habituation extra activities, and habituation extra activities in support of moral education. This research is qualitative descriptive. This research is a case study that intends to find meaning, to investigate the process and gain insight and deep understanding of individuals, groups or situations. The collection of data through observation, documentation and interview. The results of the study, namely: (1) Implementation of habituation extra activities are implemented very well and has affected the moral education of students, and (2). Habituation extra activities in supporting the moral education of students namely: the morals against Allah, to fellow human morals, morals about yourself, include; time discipline, make the heart calm, tawaduk, humble and generous